Functional ecology of the periphytic algal communities of the La Planada Reserve, in the Colombian Biogeographic Chocó - Guerrero Lizarazo, Mayra Camila (2021)
Introduction: Knowledge on the periphytic community is essential because of its central role in river primary production. Also, periphyton is a valuable bioindicator of the community. However, to the date, little is known about the functional ecology of these communities in Colombian rivers. Objective: This work sought to characterize functional aspects of the phycoperiphytic community of four lotic systems of the La Planada Natural Reserve, located in the Department of Nariño, Colombia. Methods: In May 2019, between one and three sampling sites were established in each river. Hydrological and physicochemical variables were measured. Periphyton was sample to determine the taxonomic composition of the benthic algae as well as some functional traits. From these traits, the community weighted mean (CWM) and community weighted variance (CWV) were calculated, and their relation with abiotic variables was explored using regressions, correlations, and a canonical correspondence analysis (CCA). Results: 59 genera of algae were recorded, from which 47 had its functional traits measured. The CWM of the siliceous exoskeleton trait was statistically higher in El Tejón creek. The other traits had similar CWM and CWV values in all rivers. However, the traits of the presence of mucilage and organization in filaments showed predominance in some streams. The fluctuating data of CWV in all rivers seem to indicate that these phycoperiphytic communities have no resource limitations, competition is low, and species tend to be functionally different. The environmental variables with the greatest influence were flow, water mineralization, pH, and water transparency. The hardness of the water and the presence of mucilage were associated, while the predominance of filamentous algae was related to transparency; pH positively influenced the surface/volume ratio (S/V). Conclusions: This study represents a baseline that will allow evaluating changes in the benthic algae communities in the face of possible interventions and providing guidelines for eventual actions to restore the river systems of this important region due to its high biodiversity.